THE STUDY OF THE LAWS OF FORMATION, DISTRIBUTION, AND INFLUENCE OF GROUNDWATER TO JUSTIFY SUBSTANTIATE THE PREDICTED HYDROGEOLOGICAL MODEL AT THE URBAN COMPACTED AREA - Koshliakov, O.; Dyniak, O.; Chomko, D.; Koshliakova, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The conducted researches have the purpose to develop the optimum approach which allows us to correctly estimate the hydrogeological conditions of buiding sites. The general patterns of formation, distribution and movement of groundwater within the sections of the planned and existing buildings and adjacent territories for Kyiv as an example were studied. For the study area and similar sites with complex hydrogeological conditions, which are caused by the alternation in section and in terms of layers of unsteady thickness with different filtration coefficients, it is more appropriate to use the method of mathematical modeling of geofiltration for predictive calculations. Since there is no detailed hydrogeological map of the site, it is advisable to build a natural hydrogeological model on the basis of engineering and geological survey data (groundwater levels data) for different periods reproducted by GIS. The obtained results make it possible to justify the mathematical model and to perform predictive modeling with sufficient accuracy for technogenically disturbed territories. The application of mathematical modeling allows avoiding unnecessary rough schematization of natural hydrogeological conditions, taking into account the complexity and diversity of boundary groundflow conditions, and thus give more realistic assessment of engineering measures impact on hydrogeological conditions of the territory. In order to take into account the patterns of formation, distribution and movement of groundwater for territories with dense urban development it is advisable, according to the authors, to simulate processes geofiltration according to the scheme given in this article. At the same time, the creation of scientifically sound mathematical and cartographic space-time natural hydrogeological model of the territory is the defining moment for further modeling. Application of Darcy Flow module of ArcGIS software enables to detect and specificate groundwater flow recharge and discharge conditions. This makes it possible, on the one hand, to avoid unnecessary schematization of natural hydrogeological conditions, and on the other hand, to take into account the complexity and diversity of groundflow boundary conditions, to give a more realistic assessment of possible engineering measures impact on the hydrogeological conditions of the territory during the construction.